Size-controlled cobalt ferrite nanocrystals: magnetically separable reusable nanocatalysts for selective oxidation of styrene - Jeyavani, Vijayakrishnan; Pawar, Sayali; Dadwal, Arun; Joy, Pattayil Alias; Mukherjee, Shatabdi Porel (ChemistrySelect, 2019)
Superparamagnetic cobalt ferrite (CFO) nanocrystals (NCs) with sizes similar to 6 nm and similar to 4 nm were synthesized using a facile solvothermal method using fatty acids, lauric acid and stearic acid, as the capping agents. The synthesized nanocrystals were well characterized by XRD, FT-IR, XPS, SEM and TEM. The formation mechanism was explored and it was shown that the fatty acid was actually chemisorbed as a carboxylate onto the surface of CFO NCs. The experimental results specify that the size and size distribution of the CFO NCs were highly dependent on the length of fatty acid hydrophobic chain. Corresponding changes of the magnetic properties were investigated by measuring magnetization as a function of field and temperature, which suggest that the CFO NCs were superparamagnetic in nature. The catalytic properties for the oxidation of styrene in organic medium were examined by using the synthesized CFO NCs with sizes similar to 6 nm and similar to 4 nm. The synthesized CFO NCs, well dispersible in organic media, were demonstrated to be highly catalytically active, reached 100% conversion of styrene in 12 h with similar to 77% and similar to 82% selectivity for styrene oxide respectively. The magnetic CFO nanocatalysts were easily separated and recovered from the reaction medium by an external magnet, and reused for several cycles without losing catalytic selectivity for styrene oxide.
Keywords: Cobalt ferrite; epoxidation; Fatty acids; magnetic properties; nanocrystals

MgB2/NaNO2-PVA free-standing polymer composite film as a green firework: a step towards environmental sustainability - Jeyavani, Vijayakrishnan; Kumar, Rajendra; Joy, Pattayil Alias; Mukherjee, Shatabdi Porel (Bulletin of Materials Science, 2022)
We have demonstrated a simple fabrication methodology of free-standing polymer composite film firework that sparkles, provides colour display and moderate sound, yet is less polluting. The polymer composite film fireworks are composed of magnesium boride (MgB2), sodium nitrite (NaNO2) and poly(vinyl alcohol) (PVA). This study also suggested that a flammable, explosive powder composition can be made of two very common inorganic precursors, mainly NaNO2 and MgB2 . This is the first report demonstrating composite film fireworks with new flammable composition using metal boride as a primary precursor, which can also be used in conventional fireworks fabrication, replacing the traditional fuel, mainly gunpowder. The film fireworks were free from charcoal, sulphur, metal powder and paper. Therefore, they substantially lower the odour and COx, NOx, emissions and minimize the substantial trash generated when burned. Most importantly, film firework's minimum ignition temperature and exothermic decomposition temperature are much higher than the ambient temperature; hence are safe to handle.
Keywords: Firework; free-standing film; magnesium boride (MgB2); poly(vinyl alcohol) (PVA); sodium nitrite (NaNO2)

Effect of transition metals (Mn, Co, Ni, and Zn) in size-controlled metal ferrite nanocrystals on the electrocatalytic oxygen evolution reaction - Jeyavani, Vijayakrishnan; Manoj, Shanmugasundaram; Mukherjee, Shatabdi Porel (ACS Applied Nano Materials, 2024)
Metal ferrite (MFO) M2+Fe2O4 (M2+ = Mn, Co, Ni, and Zn) nanocrystals (NCs) with a controlled size of similar to 4 nm were synthesized using stearic acid as the capping agent via a facile solvothermal method. The as-synthesized MnFe2O4 (MnFO), CoFe2O4 (CoFO), NiFe2O4 (NiFO), and ZnFe2O4 (ZnFO) NCs were characterized by XRD, FT-IR, Raman, XPS, TGA, TEM, and HRTEM analyses. The electrocatalytic oxygen evolution reaction (OER) is significant for future renewable energy to produce pure hydrogen (H-2) fuels through H2O splitting. However, because of the complex proton-coupled multielectron transfer process, it is kinetically quite challenging. Fe-containing transition metal-based electrocatalysts are well studied since it has been observed that Fe has a significant role in enhancing OER activity. It is well-known that the size and shape of the Fe/ferrite-based nanoelectrocatalyst play a vital role in electrocatalysis reactions. However, it is also critical to understand the effect of other earth-abundant and cost-effective transition metal ions (e.g., Mn, Co, Ni, and Zn) combined with Fe/ferrite NC-based OER electrocatalytic reactions while keeping the size of NCs constant and compare their electrocatalytic properties toward the development of advanced nanoelectrocatalysts, which is rarely studied to the best of the authors knowledge. Therefore, herein, the electrocatalytic properties for OER were examined by using the as-synthesized MnFO, CoFO, NiFO, and ZnFO NCs to understand the effect of metal ions (Mn, Co, Ni, and Zn) on the Fe-based nanoelectrocatalysts by keeping the size of the nanoelectrocatalysts constant at similar to 4 nm. Additionally, the influence of different substrates, e.g., carbon paper (CP) and nickel foam (NF), on the electrocatalytic activity of MFO (MnFO, CoFO, NiFO, and ZnFO) NCs was also compared. Interestingly, as an OER nanoelectrocatalyst, the CoFO NCs on the CP substrate show better electrochemical OER activity than other MFO NCs, with a Tafel slope value of 49.4 mV dec(-1), an ECSA of 112 cm(2), and a long-term stability of 24 h, which is comparatively higher than the other as-synthesized MFO NCs. On the other hand, MnFO NCs on the NF substrate show better electrochemical OER activity than the other as-synthesized MFO NCs. Therefore, this work highlights the effect of the substrate and the influence of transition metals, e.g., Mn, Co, Ni, and Zn, on size-controlled Fe-based nanoelectrocatalysts toward developing advanced OER electrocatalysts.
Keywords: Carbonpaper; electrocatalysis; Ferrites; Nickel foam; Oxygen Evolution Reaction; Size-controlled nanocrystals

Remarkable SO2 and H2S resistant ability on CO oxidation by unique Pd/WO3 3D hollow sphere nanocatalyst: correlating structure-activity relationships on SO2 exposure - Jeyavani, Vijayakrishnan; Kondhekar, Deepali; Bhati, Meema; Dev, Sahil; Joshi, Kavita; Devi, R. Nandini; Mukherjee, Shatabdi Porel (ACS Applied Energy Materials, 2024)
We report a simple inorganic route for synthesizing a Pd/WO3 3D hollow sphere nanocatalyst, where Pd nanoparticles are encapsulated and well distributed on porous tungsten oxide nanospheres. The synthesis protocol has advantages, as it requires no surfactant or stabilizing agent, Pd loading is easily tuned, and the as-synthesized nanomaterials can be directly used as catalysts for the CO oxidation reaction. The synthesized nanocatalyst exhibited 100% CO to CO2 conversion efficiency at 260 degrees C. In addition, the nanocatalyst demonstrated remarkable SO2 (3 ppm) tolerance during the CO oxidation reaction for prolonged SO2 sulfation of 1-21 h at 260-400 degrees C. This represents the longest SO2 exposure time reported to date based on a single metal Pd/support-based nanocatalyst. No decrement in CO conversion efficiency was observed even after SO2 (3 ppm) treatment for 21 h for the first time based on a single metal Pd-based nanocatalyst. Moreover, the synthesized nanocatalyst shows H2S (4 ppm), even in situ H2S tolerance during the CO oxidation reaction at 260 degrees C for 1-3 h and exhibited less sensitivity to prolonged and stringent sulfur exposure, with the highest H2S concentration and maximum 100% CO to CO2 conversion efficiency obtained after H2S treatment for the first time based on a Pd-based nanocatalyst to the best of our knowledge. The composition and structure of the R-Pd/WO3 nanocatalyst were not much influenced, even after the prolonged SO2 and H2S exposure during the CO oxidation reaction, as verified from spent catalyst analysis. Finally, our DFT-based model provides insights into understanding the observed sulfur resistance on Pd/WO3 by analyzing the underlying electronic structure. Therefore, our strategic synthesis methodology will open up many opportunities to select Pd/metal oxide-based nanomaterials for designing highly efficient, stable, and SO2/H2S-resistant nanocomposite catalyst.
Keywords: CO oxidation; DFT calculation; nanocatalyst; palladium (Pd); SO2 andH(2)S resistant ability; structure-activityrelationships; tungstenoxide (WO3)